Interview with Gabriel Abend “The Moral Background Makes the Playof Life Possible” - Abend, Gabriel (Экономическая социология, 2016)
Gabriel Abend discusses his interest in the sociology of morality and the main ideas of his book The Moral Background: An Inquiry into the History of Business Ethics [Abend 2014]. According to Abend, the business ethics discipline and its growing popularity at business schools deals not only with the tension between making money and being ethical, but with the preconditions which enable moral life: the moral background. Abend states that studying moralities and moral action in the social sciences is usually viewed through the lens of the first one, behavioral level, and the second one, normative level (moral and immoral behavior and norms, respectively), which, taken together, constitute first-order morality. Abend also points out that the “moral background” should be suggested as the third level, or second-order morality, which underlies and supports first-order morality through six dimensions. These include: the reasons for first-level morality support, the existing concepts repertoire, the subject of the moral evaluation, proper moral methods, the objectiveness of morality, and metaphysical conceptions. Some of these dimensions have a society-level organization, such as the conceptual repertoire for speaking about moralities in different languages, and some dimensions have an individual-level organization, such as the objectivity or relativity of first-order morality. Abend identifies two types of moral background that he describes as the “Christian Merchant” and the “Standards of Practice”. The “Christian Merchant” type can be characterized as an ethics of being, developing certain features of character and moral objectivism. The “Standards of Practice” is an ethics of doing, which sustains moral relativism and emphasizes moral actions with no particular attention to their motives. The “Standards of Practice” type has found its way into business schools’ curricula as a business ethics discipline that believes morality can be taught by using case studies. This approach, while maintaining the principles of corporate social responsibility, can have negative effects on society and the economy. As long as corporations suggest that ethics pays and act morally only to make a profit, there is a risk that without the payoff, they will stop acting morally. This fact causes questions to surface, not only about corporate social responsibility and ethical behavior in business, but ultimately about values and the place of morality in society at large.